(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2022)
This research aims to reveal the relationship between high- order thinking skills and general self-efficacy among a sample of students from Damascus University, Sweida Branch, and the research aims to identify the significance of the differences between individuals of the research sample according to the variable (gender, specialization), the research sample consisted of (783) (Male and female students, drawn in the available method, and the high-ranking thinking skills scale prepared by the researcher and the general self-efficacy scale of (Abdullah and Al-Aqd 2009) was used, and the analytical descriptive approach was adopted, The most results were; *- The level of high- order thinking and the general self-efficacy of the sample members was high . -Predictability of higher-order thinking through general self-efficacy. -The existence of a positive statistically significant correlation between high-order thinking skills and general self-efficacy -The absence of statistically significant differences between the averages of the research sample on the scale of high-order thinking skills according to the gender variable except after the composition in favor of males. -There are no statistically significant differences between the averages of the research sample on the measure of general self-efficacy according to the gender variable except for self-confidence in favor of females. -The existence of statistically significant differences between the averages of the research sample on the scale of high-order thinking skills according to the variable of specialization in favor of theoretical colleges. -The presence of statistically significant differences between the averages of the research sample on the measure of general self-efficacy according to the variable of specialization in favor of theoretical colleges.